Relationship between expectation management and client retention in online cognitive behavioural therapy - Ekberg, Stuart; Barnes, Rebecca; Kessler, David; Mirza, Selman; Montgomery, Alan A.; Malpass, Alice; Shaw, Alison (Cambridge University Press, 2015)
Background: Engaging clients from the outset of psychotherapy is important for therapeutic success. However, there is little research evaluating therapists’ initial attempts to engage clients in the therapeutic process. This article reports retrospective analysis of data from a trial of online cognitive behavioural therapy (CBT) for depression. Qualitative and quantitative methods were used to evaluate how therapists manage clients’ expectations at the outset of therapy and its relationship with client retention in the therapeutic intervention. Aims: To develop a system to codify expectation management in initial sessions of online CBT and evaluate its relationship with retention. Method: Initial qualitative research using conversation analysis identified three communication practices used by therapists at the start of first sessions: no expectation management, some expectation management, and comprehensive expectation management. These findings were developed into a coding scheme that enabled substantial inter-rater agreement (weighted Kappa = 0.78; 95% CI: 0.52 to 0.94) and was applied to all trial data. Results: Adjusting for a range of client variables, primary analysis of data from 147 clients found comprehensive expectation management was associated with clients remaining in therapy for 1.4 sessions longer than those who received no expectation management (95% CI: -0.2 to 3.0). This finding was supported by a sensitivity analysis including an additional 21 clients (1.6 sessions, 95% CI: 0.2 to 3.1). Conclusions: Using a combination of qualitative and quantitative methods, this study suggests a relationship between expectation management and client retention in online CBT for depression, which has implications for professional practice. A larger prospective study would enable a more precise estimate of retention.